Heroes and Horses : Tales of the Bluegrass - Ardery, Philip, 1914- (Book collections on Project MUSE., 2004)
War hero. Lawyer. U.S. Senate candidate. Horse lover. Farm boy. Fundraiser. To this impressive list add one more role ably filled by Philip Ardery: master storyteller. Heroes and Horses presents a series of delightful vignettes evoking a way of life almost beyond recall. Bourbon County, the touchstone for Ardery's life, is the center that holds together the tales in the collection. Stories about Ardery's family home, ""Rocclicgan, "" boyhood activities on the farm, and the servants' kitchen gossip paint vivid portraits of a lost time in Kentucky's history. Though the Ardery family and most of th.